Inkulturasi Budaya Jawa Pada Gereja Katolik Hati Kudus Tuhan Yesus Ganjuran, Bantulan, Daerah Istimewa Yogyakarta - Billy Apriansyah; Siti Nadroh (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2024)
The results of this study found that referring to the question of the problem formulation, namely what are the forms of Javanese cultural inculturation in Ganjuran Church and how does the community respond to Javanese cultural inculturation in Ganjuran Church. First, in the Christian liturgy, this is very much in line with Smutzer's wishes, which really wanted the Church to conceptualize Javanese culture because Smutzer's love for Javanese culture was so much that the Church of the Sacred Heart of the Lord Jesus was made This became a church with the concept of Javanese cultural architecture, many such as ornaments, religious, there are even temples that are included in the building. The two churches of the Sacred Heart of the Lord Jesus, Ganjuran, use a form of Javanese cultural inculturation model which is indeed located in Yogyakarta can be seen in terms of architecture and buildings that use designs such as the Yogyakarta palace in the main building to art such as relics and ornaments that are formed also use Javanese culture because indeed this design involves the sultanate of Ngayogyakarta itself and is approved to be built to resemble the palace building. Third, the response of the people who were there did not mind even they were very amazed at what was achieved in the design of the Ganjuran Church. And Laurens in his theory of inculturation is in line with what is built on Church of the Sacred Heart of the Lord Jesus Ganjuran.